EFEK INTERVENSI MINUMAN TEMPE TERHADAP PENURUNAN KADAR LOW DENSITY LIPOPROTEIN - Wirawanti, Ika Wirya; Hardinsyah, Hardinsyah; Briawan, Dodik; Astawan, Made (Jurnal Gizi dan Pangan, 2017)
The aim of this study was to analyze the effect of tempe drink intervention on lipid profile of hypercholesterolemic subjects. This study used a Randomized Controlled Trial (RCT) design with 51 males and females subjects with the inclusion criterias were adults aged 25-55 years, not being menopause and pregnant, total cholesterol levels ≥200 mg/dl and signed informed consent. The subjects were divided into three treatments - Tempe Drink of A (TDA) formulated from local sprouted soybean, Tempe Drink of B (TDB) formulated from imported soybean and control. The tempe drink was given three glasses a day for four weeks, contained at least 25 g of protein/day. The control treatment was not given the tempe drink. Lipid profile (total cholesterol, low density lipoprotein (LDL), high density lipoprotein (HDL) and triglycerides (TG)) was collected before and after  intervention. The results showed that both TDA and TDB decreased total cholesterol, LDL, and TG of subjects, respectively 26.7 mg/dl and 17.3 mg/dl; 3.6 mg/dl and 1.0 mg/dl; and 16.2 mg/dl and 3.7 mg/dl compared to control subjects, but did not increase HDL of subjects. This implies that tempe drink had beneficial health effect on lowering total cholesterol, LDL and TG.